Pemanfaatan Jantung Pisang Mulu Bebe dengan Penambahan Daging Ikan Tuna sebagai Bahan Pembuatan Bakso di Dusun Tuwokona, Halmahera Barat - Albaar, Nurjana; Rasulu, Hamidin; Abu Rahmat Ibrahim; Janiah Husen; Hayun Abdullah; Abdul Kadir Kamaluddin (Program Studi Kehutanan, Universitas Khairun, 2024)
Utilizing local potential is very important. As an example of how creative economic empowerment can be done through making processed products based on village potential. The activities carried out by the PKM team at the Faculty of Agriculture, Khairun University aim to help MSMEs, especially the Tuwokona Hamlet Farmers Group, in resolving the obstacles they face. The method used in this activity was to observe the village's potential, followed by interviews, then training and assistance activities were carried out in making meatball products made from mulu bebe banana blossoms and tuna fish meat. So the result through the implementation of this PKM activity is that the potential of local resources can be utilized optimally and can provide added value to the community both in terms of increasing economic value and food diversity. The use of Mulu Bebe banana blossoms and tuna fish meat as ingredients for making meatballs will provide added value to local food sources, so that through this training the people gathered in the Tuwokona Hamlet Farmers Group will be more productive in diversifying their products, one of which is enriched banana blossom meatballs. with the addition of tuna meat. In conclusion, assistance for the Tuwokona Hamlet farmer group is very necessary in improving their skills so that they can produce meatball products that are economically valuable and have high nutritional value.